2020
DOI: 10.1111/cas.14753
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for esophageal iodine‐unstained lesions and changing trends among Japanese alcohol‐dependent men (2003‐2018)

Abstract: Globally, a decreasing incidence of male esophageal squamous cell carcinoma (ESCC) has been observed in recent decades. We evaluated the determinants of esophageal distinct iodine‐unstained lesions (DIULs), high‐cancer‐risk lesions and ESCC, among 3858 Japanese alcohol‐dependent men (40‐79 years) who underwent chromoendoscopic screening between 2003 and 2018. The initial screening detected DIULs ≥ 5 mm in 541 patients (dysplasia in 319 and SCC in 129) and multiple DIULs in 640. The detection rates for DIULs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…This result may be due to the overall longer postoperative survival time of LSCC patients compared with other upper gastrointestinal tumors such as esophagus and gastric cancer. [18][19][20] Although ADH1B rs3811802 and rs1229982 were polymorphic in our enrolled patients, our analysis revealed no association with LSCC.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This result may be due to the overall longer postoperative survival time of LSCC patients compared with other upper gastrointestinal tumors such as esophagus and gastric cancer. [18][19][20] Although ADH1B rs3811802 and rs1229982 were polymorphic in our enrolled patients, our analysis revealed no association with LSCC.…”
Section: Discussioncontrasting
confidence: 65%
“…Interestingly, we found that the important functional polymorphism of ADH1B , rs1229984, was also associated only with the higher recurrence of LSCC (HR = 2.664, 95% CI = 1.393–5.095, p = 0.003), whereas it showed no significant effects on OS. This result may be due to the overall longer postoperative survival time of LSCC patients compared with other upper gastrointestinal tumors such as esophagus and gastric cancer 18–20 . Although ADH1B rs3811802 and rs1229982 were polymorphic in our enrolled patients, our analysis revealed no association with LSCC.…”
Section: Discussionmentioning
confidence: 58%